Integrative approach in the study of ethnic (national) identity concept - Dossova, N S; Kambarov B.K.,, K B; Mukatova, А М (Journal of Oriental Studies, 2016)
The article is dedicated to the study of identity, ethnic (national) identityin the modern world. The need for an integrative approach based ona combination of private approaches is shown on the analysis of the mainapproaches to the study of ethnic identity.